Real-Time Three-Dimensional Knee Moment Estimation in Knee Osteoarthritis: Toward Biodynamic Knee Osteoarthritis Evaluation and Training - Kang, Sang Hoon; Lee, Song Joo; Press, Joel M.; Zhang, Li-Qun (Institute of Electrical and Electronics Engineers, 2019)
We investigated differences in knee kinetic variables (external knee adduction, flexion, internal rotation moments, and impulses) between patients with knee osteoarthritis (KOA) and healthy controls during stepping on a custom elliptical trainer; and searched knee kinetic variable candidates for real-time biofeedback and for complementing diagnosis/evaluation on the elliptical trainer based on the knee kinetic variables' associations with the knee injury and osteoarthritis outcome score (KOOS). Furthermore, we explored potential gait re-training strategies on the elliptical trainer by investigating the knee kinetic variables' associations with 3-D ankle angles. The knee kinetic variables and ankle angles were determined in real-time in a patient group of 10 patients with KOA and an age-and sex-matched control group of 10 healthy subjects. The mean peak external knee adduction moment of the patient group was 47% higher than that of the control group. The KOOS-Sports and Recreational Activities and KOOS-Pain scores were found to be significantly associated with the knee kinetic variables. All the ankle angles were associated with the knee kinetic variables. The findings support the use of the knee kinetic variables on the elliptical trainer to complement KOA diagnosis quantitatively and provide potential real-time KOA gait re-training strategies/guides. Index